Center-Pivot-Irrigated Alfalfa Cost-Return Budget in Western Kansas - Dumler, Troy J.; Thompson, Curtis R.; Stockton, Roger (My University, 2003)
This publication projects a budget that reflects expected income and costs based on center-pivot-irrigated alfalfa production in western Kansas.
MF584_2003_10
Keywords: MF584; Economics; Crops; MF